Stone emplacement in early Scottish churches: evidence of Early Christian craftsmanship (Proceedings of the Society of Antiquaries of Scotland, 2007)
Although it has become customary to suggest that the first stone ecclesiastical buildings in Scotland date from the earliest 12th century, this examination of stone emplacement indicates that English Saxon-style craftsmanship is evident in a number of early Scottish churches. It seems probable that, as in England, pre-Norman Conquest masons in Scotland chose to emplace many of their stones, in structures like quoins and jambs, with the bedding orientated vertically. The recognition of the existence of pre-12th century stone churches in Scotland is consistent with the prevalence of other forms of early Christian stoneworking in that period.